Angular Distribution of Characteristic Radiation Following the Excitation of He-Like Uranium in Relativistic Collisions - Alexandre Gumberidze; Daniel B. Thorn; Andrey Surzhykov; Christopher J. Fontes; Dariusz Banaś; Heinrich F. Beyer; Weidong Chen; Robert E. Grisenti; Siegbert Hagmann; Regina Hess; Pierre-Michel Hillenbrand; Paul Indelicato; et al. (Atoms, 2021)
In this paper, we present an experimental and theoretical study of excitation processes for the heaviest stable helium-like ion, that is, He-like uranium occurring in relativistic collisions with hydrogen and argon targets. In particular, we concentrate on angular distributions of the characteristic K<semantics>α</semantics> radiation following the K → L excitation of He-like uranium. We pay special attention to the magnetic sub-level population of the excited <semantics>1s2lj</semantics> states, which is directly related to the angular distribution of the characteristic K<semantics>α</semantics> radiation. We show that the experimental data can be well described by calculations taking into account the excitation by the target nucleus as well as by the target electrons. Moreover, we demonstrate for the first time an important influence of the electron-impact excitation process on the angular distributions of the K<semantics>α</semantics> radiation produced by excitation of He-like uranium in collisions with different targets.